Thermal and Rheological Characterization of Aqueous Nanofluids Based on Reduced Graphene Oxide (Rgo) with Manganese Dioxide Nanocomposites mno2 - Vasco-Calle, D; Singh, D; Ramirez-Navarro, M; Ramirez-Navarro, M; Lozano-Steinmetz, F; Vivas, L (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Nanofluids have become of interest in recent years thanks to their improved thermal properties, which make them especially interesting for microchannel heat sink applications. In this study, we prepared two aqueous nanofluids based on reduced graphene oxide (rGO) decorated with manganese dioxide (MnO (Formula presented.)) at a concentration of 0.1 wt.%. The difference between the two nanofluids was in the preparation of the reduced graphene oxide decorated with MnO (Formula presented.). In the first case, the manganese salt was mixed with ascorbic acid before GO reduction with NaOH, and in the second case, the GO reduction with NaOH occurred under ascorbic acid. Ascorbic acid not only plays the role of a non-toxic and ecofriendly reducing agent but also acts as an important parameter to control the reaction kinetics. The structural, microstructural and spectral characterizations of the MnO (Formula presented.) /rGO nanocomposite were conducted via X-ray diffractometry (XRD), Raman spectroscopy, FT-IR, TEM, SEM and EDS analyses. Moreover, the synthesized MnO (Formula presented.) /rGO nanocomposites were utilized as nanofluids and their stability, thermal conductivity and rheological behaviors were studied. The thermal conductivity of the MnO (Formula presented.) /rGO and MnO (Formula presented.) AsA/rGO nanofluids was 17% and 14.8% higher than that of water for the average temperature range, respectively, but their viscosity remained statistically equal to that of water. Moreover, both nanofluids presented Newtonian behavior in the analyzed shear rate range. Therefore, both MnO (Formula presented.) /rGO and MnO (Formula presented.) AsA/rGO nanofluids are promising alternatives for use in applications with micro- and millichannel heat sinks. © 2022 by the authors.